Highly Sensitive T-Shaped Quartz Tuning Fork Based CH4-Light-Induced Thermoelastic Spectroscopy Sensor with Hydrogen and Helium Enhanced Technique - Yuanzhi Wang; Ying He; Shunda Qiao; Xiaoming Duan; Yufei Ma (Sensors)
In this paper, a highly sensitive methane (CH4) sensor based on light-induced thermoelastic spectroscopy (LITES) and a T-shaped quartz tuning fork (QTF) with hydrogen (H2) and helium (He) enhancement techniques are reported for the first time. The low resonant frequency self-designed T-shaped QTF was exploited for improving the energy accumulation time. H2 and He were utilized as surrounding gases for the T-shaped QTF to minimize energy loss, thereby enhancing the sensitivity of the LITES sensor. Additionally, a fiber-coupled multi-pass cell (FC-MPC) with a 40 m optical length was utilized to improve the optical absorption of CH4. The frequency response of the T-shaped QTF with different concentrations of H2 and He was investigated, and the Q factor in the H2 and He environment increased significantly. Compared to operating QTF in a nitrogen (N2) environment, the signal amplitude was enhanced by 2.9 times and 1.9 times in pure H2 and He environments, respectively. This enhancement corresponded to a minimum detection limit (MDL) of 80.3 ppb and 113.6 ppb. Under different CH4 concentrations, the T-shaped QTF-based H2-enhanced CH4-LITES sensor showed an excellent linear response. Furthermore, through Allan deviation analysis, the MDL of the T-shaped QTF-based H2-enhanced CH4-LITES can reach 38 ppb with an 800 s integration time.